Delay SIR model with nonlinear incident rate and varying total population - Rujira Ouncharoen (2018)
Recently, models describing the behavior of SIR epidemic with nonlinear incident rate have been revisited. We study the behavior of the model with time delay in which the total population size varies. Lyapunov functions are constructed to establish the global asymptotic stability of all steady states of the model. Numerical simulations are shown to confirm the main results.